Improvement and implementation of the physical development plan for young volleyball players - Yin Yingying, (Theory and Practice of Physical Culture, 2025)
Objective of the study. The subject of the analysis in this paper is the study of the prospects for improving the physical fitness of young volleyball players, taking into account the specifics of their training process. Methods and structure of the study.Methodsusedin the research:studyandgeneralization of theoreticaldata;application of a methodologicalapproachtoanalysis.Theoreticalmaterials,aswell as currenttrainingprogramsforyoungvolleyball players usedinspecializedsportsschools, wereconsideredasanempiricalbase.Basedon the resultsobtained, it can be concludedthat the purposefuldevelopment of physicalqualities in youngvolleyball players is essential. Results and conclusions. The introduction of such approaches can have a positive impact both on the individual achievements of athletes and on the overall level of development of volleyball in the country, region and in the international arena.